Applying strength and conditioning practices to young athletes - Lloyd, R. S.; Radnor, J. M.; Moeskops, S.; Meyers, R. W.; Read, P. J.; Oliver, J. L. (Routledge handbook of strength and conditioning: Sport-specific programming for high performance, 2018)
Ever since Sid Robinson conducted the first experiment examining the response of children to exercise (Robinson, 1938), the field of paediatric exercise science has continued to advance our understanding of the way in which children respond to training. Now, nearly 80 years since Robinson's seminal work, the current evidence base shows that children differ to adults in terms of their acute cardiorespiratory response to exercise (Armstrong et al., 2015), metabolic and hormonal responses during exercise (Boisseau and Delamarche, 2000), ability to voluntarily activate muscle (Dotan et al., 2012), and the way in which they recover from high-intensity exercise (Falk and Dotan, 2006). Due to these physiological differences, adult-based training programmes should not be superimposed on young athletes, but rather training prescription should be commensurate with a child`s levels of technical competency, training age, psychosocial maturity and stage of maturation.